Technical feasibility for pilot scale production of kamias (Averrhoa bilimbi Linn.) as raisin substitute - Avellaneda, Rosario G.; Acevedo, Teresita P. (1976)
A study was conducted to determine the technical feasibility of producing kamiasin, (Philippine raisin substitute) on a pilot scale level. This was accomplished by standardizing a kitchen-tested procedure on the production of kamiasin then later, translating the standardized procedure into pilot scale (ten times the level for laboratory scale). Results of objective and subjective tests indicated that the sample which was stepped up to only 45°Bx using a combination of brown sugar and molasses and sun dried for 16 to 24 hours more nearly resembled real raisins in terms of their appearance, flavor and moisture content. The kamiasin was incorporated into raisins cookies and empanaditas, highly accepted products utilizing raisins. Subjective tests results indicated that cookies using real raisins and kamiasin were not significantly different and when incorporated into empanaditas was preferred over real raisins.
Appendices: leaves 58-59.
Thesis (BSFT)--University of the Philippines, Quezon City.
Typescript.
Keywords: Kamias; Fruit processing; Raisins